Faktor-Faktor yang Mempengaruhi Perilaku Nelayan Artisanal dalam Pemanfaatan Sumberdaya Perikanan di Pantai Utara Provinsi Jawa Barat - Prihandoko Prihandoko; Amri Jahi; I Gusti Putu Purnaba; Luky Adrianto; Iwan Tjitradjaja (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2012)
This study aims to estimate accurately the behavior using the Theory of Planned Behavior perspective of artisanal fishermen in Indonesi., The population of artisanal fishermen in the northern coast of West Java Province 10,404. Techniques for sampling by cluster random sampling clusters with the number of household sample of 400 artisanal fishermen. Data was collected using a questionnaire interview further processed using the program structural equation model (SEM) and LISREL 8:54. The conclusion of this study were (1) Theory of Planned Behavior perspective can be used to view the behavior intention of artisanal fishermen in the northern coast of West Java province; (2) the coefficient of determination between the attitude variables, subjective norm, perceived behavior control to variable behavior intention at 0,64. Meanwhile the influence of variables on behavior intention to behavior by 0,68 indicates that it is not fully manifested the behavior intention in accordance with the behavior of fishermen in their fishing activities, (3) that explains the study's findings about contribution of the Theory Planned Behavior perspective to the problem of coastal common resource and can contribute to the activities of co-management of fisheries in Indonesia, especially in communities in the study area on the northern coast of West Java Province.Keywords: artisanal fishermen behavior, behavior intention, attitude, subjective norm, perceived behavior control